ANALYSIS OF ECONOMIC EFFICIENCY OF INVESTMENT PROJECTS IN UZBEKISTAN: ON THE EXAMPLE OF INFRASTRUCTURE PROJECTS - Teshaboev Jamshidbek , Kudratillaevich (THE INNOVATION ECONOMY, 2025)
This article analyzes the economic efficiency of investment projects in Uzbekistan, focusing on infrastructure projects in transport and energy sectors. The study examines cost-benefit ratios, return on investment, and social impacts. A mixed-methods approach was employed, combining qualitative analysis (of legislation and project documents) and quantitative analysis (of statistical data for 2020–2024). Findings indicate that infrastructure projects contribute to economic growth, but financial constraints, legislative ambiguities, and skill shortages persist. Recommendations tailored to Uzbekistan’s context are provided.